Choosing a Suitable Consensus Algorithm for Blockchain Applications: A Review of Factors and Challenges - Jain, Rajat; Borkar, Pradnya; Deshmukh, Priyanshu; Badhiye, Sagarkumar; Nimje, Kritika; Gupta, Kapil (International Journal of Intelligent Systems and Applications in Engineering, 2024)
Consensus algorithms are essential for ensuring the security, reliability, and performance of blockchain systems, which are distributed ledgers that store and process transactions among multiple nodes. However, choosing a suitable consensus algorithm for a blockchain application is a challenging task, as different algorithms have different trade-offs and limitations in terms of scalability, performance, and security. This paper reviews and compares various consensus algorithms, such as Byzantine fault tolerance (BFT), practical Byzantine fault tolerance (PBFT), and their improved variants, based on multiple criteria, such as goals, power consumption, cost, CAP theorem, application scenarios, and research directions. The paper provides a comprehensive overview of the current state and future challenges of consensus algorithms for blockchain technology and offers some guidelines and recommendations for selecting the best algorithm for different blockchain applications.